English Speaking Practice beyond the Classroom: A Systematic Literature Review of Informal Learning Activities, Digital Platforms, and Learner Factors in EFL Contexts - Siti Aminah; Ummi Rasyidah (British (Jurnal Bahasa dan Sastra Inggris), 2026)
This study investigates the role of extracurricular and beyond-the-classroom speaking practices in developing English speaking proficiency among English as a Foreign Language (EFL) learners. Employing a systematic literature review (SLR) design following the PRISMA 2020 framework (Page et al., 2021), the study synthesizes 33 empirical studies published between 2020 and 2024 to examine how extracurricular activities are conducted. Thematic synthesis reveals five major themes: (1) English clubs as primary extracurricular speaking environments; (2) communicative and interactive speaking activities; (3) digital and technology-mediated speaking practices; (4) affective dimensions, including anxiety reduction and willingness to communicate; and (5) extramural English exposure and learner autonomy. Findings demonstrate that extracurricular speaking environments function as integrated communicative ecosystems combining social interaction, learner autonomy, digital mediation, and authentic language exposure. The novelty of this review lies in its comprehensive synthesis of beyond-the-classroom speaking development from ecological, technological, affective, and communicative perspectives, contributing theoretical insights and pedagogical recommendations for EFL speaking instruction.